2017
DOI: 10.1186/s13044-017-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyalinizing trabecular tumor of the thyroid gland and its significant diagnostic issue

Abstract: BackgroundHyalinizing trabecular tumors (HTT) are rare follicular cell-derived tumors of the thyroid gland that are infrequently reported in otolaryngology literature. We present here an interesting case of HTT which provides the basis for review of this entity’s clinical characteristics, criteria useful in making the diagnosis, and any currently available therapeutic modalities.Case presentationA 70-year-old Caucasian female underwent a CT scan of her chest and was incidentally found to have a nodule within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The cytological interpretation of HTT is equally difficult. The difficulty in rendering a cytological diagnosis of HTT is caused by the cytomorphological features of nuclear pseudoinclusions, nuclear grooves, and hyaline material that can result in a false‐positive diagnosis of PTC or MTC . Different published series including cytological samples of HTT have documented that up to 60% of cases were diagnosed as positive and/or suspicious for malignancy, despite the fact that the samples had a lack of papillary structures and that lesions exhibited elongated nuclei associated with acellular hyaline stroma .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cytological interpretation of HTT is equally difficult. The difficulty in rendering a cytological diagnosis of HTT is caused by the cytomorphological features of nuclear pseudoinclusions, nuclear grooves, and hyaline material that can result in a false‐positive diagnosis of PTC or MTC . Different published series including cytological samples of HTT have documented that up to 60% of cases were diagnosed as positive and/or suspicious for malignancy, despite the fact that the samples had a lack of papillary structures and that lesions exhibited elongated nuclei associated with acellular hyaline stroma .…”
Section: Discussionmentioning
confidence: 99%
“…Several cytomorphological features have been recognized with HTT including cellular aggregates arranged around hyaline material, cells with a low nuclear/cytoplasmic ratio, fine chromatin (that differs from the optical clear chromatin seen in PTC), abundant nuclear pseudoinclusions and grooves, and samples with a bloody background . Despite the difficulty in diagnosing HTT with FNA due to these overlapping cytomorphological features, Carney et al demonstrated that HTT could be cytologically diagnosed in 72% of their cases …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations